S.M. Ali, a commemorative volume - Ali, S. M., 1928-1993; Ally, Fowzia; Isalāma, Saiẏada Manajurula
Collection of editorials, tributes on S.M. Ali, 1928-1993, a journalist from Bangladesh; also includes biographical sketches.